Discourse, religion, and youth identity: A critical analysis of Qur’anic intertextuality in popular Indonesian Islamic novels - Zulfadhli, Zulfadhli; Ulya, Ridha Hasnul; Nasution, Muhammad Ismail; Dhika JR, Vicno Triwira; Pramesti, Utami Dewi; Putri, Delsy Arma (Research Journal in Advanced Humanities, 2026)
The researcher investigated the idea of da‘wah obsession within Habiburrahman El Shirazy’s novels, Ayat-Ayat Cinta and Ketika Cinta Bertasbih. Utilizing a qualitative method that combined interpretative lens of Ricoeur’s hermeneutics, thematic tafsir (ma‘duhi) and Fairclough’s critical discourse analysis, the researcher categorized 21 verses referenced throughout the two aforementioned texts in four da‘wah categories: tawhid, sharia, akhlaq, and amar ma‘ruf nahi munkar. The results of the study indicate that there is a progressive strategic development in El Shirazy’s da‘wah vision. Ayat-Ayat Cinta presents ethical da‘wah defined purely by the tenets of love and family responsibility, while Ketika Cinta Bertasbih’s focus shifts toward a rationalistic concept of tawhid along with a greater emphasis on social activism. As a result, while the integration of scripture was used as a narrative persuasion strategy for the post-secular Muslim generation, it was not utilized simply for the purpose of commodification. The researcher concludes that both novels represent an example of novelistic cultural ijtihad and therefore allow for the transformation of popular literature into an all-inclusive da‘wah environment, thus demonstrating Islam as rahmatan lil ‘ā lamin.